2006
DOI: 10.1080/02770900500448597
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Its Relationship with Asthma Prevalence and Severity in Adolescents from Southern Brazil

Abstract: Obesity has been pointed out as a risk factor for higher prevalence of asthma and asthma-related symptoms in adolescents. The objective was to evaluate the relationship between the prevalence of asthma and obesity in adolescents living in Santa Maria and surroundings (state of Rio Grande do Sul, southern Brazil), applying the International Study of Asthma and Allergies in Childhood (ISAAC) protocol. A total of 4,010 of 6,123 schoolchildren, 13 to 14 years of age, enrolled in the ISAAC phase III protocol (asthm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1
10

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 25 publications
5
40
1
10
Order By: Relevance
“…These findings are consistent with other published studies documenting an overlap between asthma and overweight status (39,40), including similar casecontrol designs (41). Interestingly, disproportionately higher rates of overweight status were found consistently across males and females, while others have found sex differences in the relationship between asthma and obesity across different ages (42,43). Moreover, this is one of the first studies to report differences in obesity rates in a matched cohort design controlling for key demographic variables, such as sex, age, and racial/ethnic background.…”
Section: Discussionsupporting
confidence: 82%
“…These findings are consistent with other published studies documenting an overlap between asthma and overweight status (39,40), including similar casecontrol designs (41). Interestingly, disproportionately higher rates of overweight status were found consistently across males and females, while others have found sex differences in the relationship between asthma and obesity across different ages (42,43). Moreover, this is one of the first studies to report differences in obesity rates in a matched cohort design controlling for key demographic variables, such as sex, age, and racial/ethnic background.…”
Section: Discussionsupporting
confidence: 82%
“…Cassol et al, 12 on the other hand, found a positive association between obesity and the prevalence of asthma in 4,010 adolescents in southern Brazil. Vlaski et al 16 found that being overweight was significantly associated with an increased risk of having asthma (OR: 2.36, 95% CI: 1.02-5.44, p=0.04).…”
Section: Resultsmentioning
confidence: 99%
“…9 In addition, several studies have assessed the possibility of obesity increasing the risk for development of asthma and other obstructive respiratory diseases. [10][11][12][13][14][15][16] The possible mechanisms for this relationship include airway inflammation, produced by substances in adipose tissue, hormonal influences and changes in physical activity. 10 Obesity can also cause changes in lung function, leading to restrictive respiratory disorders caused by parenchymal lung disease or disorders of the chest wall.…”
Section: Introductionmentioning
confidence: 99%
“…Obezitenin astım üzerine etkisini değerlendiren çalış-malarda, önceleri daha çok astım şiddeti araştırılmış-tır (5,6) . Fakat 2007'deki National Asthma Education and Prevention Program (NAEPP) klavuzunda, AKT'nin astımlı hastaların uzun dönem izleminde şiddettin yerine kullanılması önerilmiştir.…”
Section: İstatistiksel Analizunclassified
“…'deki zorlu ekspirasyon volümü (FEV1) ve zorlu vital kapasite (FVC)'de azalma, kronik inflamasyona neden olması (adipokinlerden leptin düzeylerinde artma, adiponektin düzeylerinde azalma, oksidatif streste artma), etiyolojideki epigenetik ve genetik benzerlikler, hormonal değişiklikler (progesteron azalması ve buna bağlı olarak beta-2 reseptör yanıtında azalma), komorbid hastalıklar (obezitenin astımı tetikleyebilen gastroö-zefageal reflü (GER), obsruktif uyku apne sendromu (OUAS), dislipidemi, tip 2 diabetes mellitus ve hipertansiyona neden olması) ve çevresel-davranışsal benzerliklerdir (4) . Öne sürülen tüm bu teorilerle obezite, astım şiddetini ve solunum fonksiyonlarını etkileyebilmektedir (5,6) . Vücut kitle indeksi (VKİ) obezitenin değerlendirilmesinde yaygın olarak kullanıl-maktadır.…”
Section: Introductionunclassified